Quisquis Amat Valeat! (Whoever Loves, May He be Well) Why Love and Passion Are Important for the Well-Being of the Immune System - D'Acquisto, Fulvio (Frontiers in Education, 2019)
“Quisquis amat valeat; pereat qui non-scit amare; bis tanti pereat, quisquis amare vetat”—(Whoever loves, may he be well; may he perish who does not know how to love; may he perish twice as much whoever forbids loving). This graffiti was found in the old city of Pompei. The author is unknown. Possibly a poet but quite possibly an ordinary citizen who in the spur of their passion wanted to share with everyone a pearl of wisdom. Amare in Latin is “to love” and, as in English, it is not just about sex or romance, but also about passion for a cause or an ideal. The Latins knew that to be in love, to have a passion, is to be healthy in the body and as well as in the mind. In this article, I hypothesize that the lack of passion and love in life is one of the main causes of modern diseases and specifically immune/inflammatory diseases. I will explore in layman terms the limitations of specifically focusing on controlling bodily functions without considering the social and emotional dimensions of one's life. Lastly, I will highlight the importance of cooperative research, engagement with the public and education as the way forward for a more effective and democratic model for new socially inclusive therapies.